Individuality, kin similarity and experimental playback of contact calls in cooperatively breeding riflemen. Issue 4 (2nd October 2019) - Khwaja, Nyil; Briskie, James V.; Hatchwell, Ben J.
ABSTRACT: Riflemen/tītipounamu ( Acanthisitta chloris ) are kin-based cooperatively breeding birds, which appear able to recognise their relatives. Here, we investigate the potential for vocalisations to act as recognition cues in riflemen. We identified an appropriate contact call and recorded it at the nest from 19 adult riflemen. Measurements of call characteristics were individually repeatable. In addition, call similarity was significantly correlated with relatedness among all birds and among males. Thus, in principle, these contact calls contain sufficient information for individual recognition of familiar kin, and some assessment of relatedness between unfamiliar birds. To test whether riflemen responded differently to calls of kin, we broadcast calls of relatives and non-relatives as separate treatments in a playback experiment. Focal birds rarely responded aggressively or affiliatively, and their tendency to do so was unrelated to treatment. We conclude that zip calls are suitable kin recognition cues, but whether they are used as such remains unknown.